The MMT of Elbow Flexion and the AFE Predict Impairment and Disability at 3 Weeks in Patients With Acute Stroke - Ueda, Shujiro; Aoki, Hiroko; Yasuda, Yumiko; Nishiyama, Ayumi; Hayashi, Yusuke; Honaga, Kaoru; Tanuma, Akira; Takakura, Tomokazu; Kurosu, Akihiro; Hatori, Kozo; Hayashi, Akito; Fujiwara, Toshiyuki (Frontiers in Neurology, 2022)
Objective This study aimed to investigate whether upper extremity motor function assessment within 72 h from stroke onset can predict the functional outcomes of the upper extremity. Design This was a prospective, cohort study of patients with a first unilateral hemispheric stroke between May 2018 and March 2020. The motor arm item of the National Institutes of Health Stroke Scale, manual muscle testing of the elbow and forearm, and active finger extension scale were assessed within 72 h after stroke onset. The Fugl-Meyer assessment upper extremity motor score and action research arm test were assessed at discharge from the acute hospital. Multiple regression analysis was used to study predictors of upper extremity motor function at discharge from the acute hospital. The adjustment variables included age, sex, thumb localizing test, and visuospatial function. Results Sixty acute stroke patients were recruited. The model with the highest coefficient of determination for the Fugl-Meyer assessment upper extremity motor score at discharge was the elbow flexion model (R2 = 0.76), followed by the active finger extension model (R2 = 0.69). For the action research arm test, the highest model was the active finger extension model (R2 = 0.64), followed by the elbow flexion model (R2 = 0.63). Conclusion The manual muscle testing of elbow flexion and the active finger extension may be useful for predicting impairment and disability at 3 weeks in patients with acute stroke.